PERAN CENTER FOR INTERNASIONAL FORESTRY RESEARCH (CIFOR) DI INDONESIA TERKAIT MEKANISME REDUCING EMISSION FROM DEFORESTATION AND FOREST DEGRADATION (REDD) 2007-2014 - Ibnu Hajar; Tri Joko Waluyo (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research aimed to cexplain the role of an international organization CIFOR at a Reducing Emissions from Deforestation and Forest Degradation in Indonesia. The organization is an organization that focused on forestry research. Since the issue of climate change become the attention of the world and also the attention of student. Indonesia became one of the foremost in support of the issue. In COP 13 which is a string of framework under the UNFCCC appears a scheme for Reducing Emissions from Deforestation and Forest Degradation. The scheme also is the reference Indonesia and other countries for support to solve the problem of climate change, such a scheme known as REDD. The theory used in this paper is the role theory. In this research, The method used of qualitative methods, qualitative research is a descriptive understanding. This research found that the role of international organizations in supporting and contributing to problem a country can be as Motivator, communicator, and Fasilitator.Keywords: Peran, Perubahan Iklim, CIFOR, COP 13,REDD, UNFCCC, Deforestasi, Degradasi.